Tradisi Menjelang Pernikahan Perspektif Paradigma Generasi Muda di Desa Brengkok, Brondong, Lamongan - Fahrudin Fahrudin (State Islamic University (UIN) of Sunan Ampel, 2021)
The younger generation is often considered to be against the establishment running in the community's social environment. For example, in the context of traditions related to ceremonial pre-wedding, there is a new perspective on these various events. For the older generation, this condition can be considered a contradiction to the legacy that has been running in society. More specifically, such a paradigm is also symptomatic among the younger generation of Brengkok Village. This study tries to dig deeper into the paradigm of the younger generation of Brengkok village. By using interview techniques with the younger generation in Brengkok village, it is hoped that they will be able to present more comprehensive data. The interviews were then analyzed using Max Weber's approach to social action theory. The paradigm that exists in the younger generation of Brengkok Village is, of course, based on rational reasons for traditions that have been established and run across generations. Something that has been considered a patent value by the older generation. When the current younger generation is in a position as the older generation, it will certainly give a different touch to the passage of traditions leading up to the wedding. The various rational reasons put forward will become considerations that have more value, which in the end, will answer the anxiety of the older generation about the existence of this tradition.